The patron saint of liars - Patchett, Ann (Boston : Mariner Books, 2011)
A pregnant woman leaves her husband and moves to St. Elizabeth's, a Catholic home for unwed mothers in Kentucky, to begin a new life.
Originally published: Boston : Houghton Mifflin, 1992.
Keywords: Unmarried mothers -- Fiction; Mothers and daughters -- Fiction; Catholics -- Fiction; Nuns -- Fiction; Kentucky -- Fiction